Modulation of gut microbiota: The effects of a fruits and vegetables supplement - Lakshmanan, Arun Prasath; Mingione, Alessandra; Pivari, Francesca; Dogliotti, Elena; Brasacchio, Caterina; Murugesan, Selvasankar; Cusi, Daniele; Lazzaroni, Monica; Soldati, Laura; Terranegra, Annalisa (Frontiers in Nutrition, 2022)
The consumption of an optimal amount of fruits and vegetables is known to improve physical fitness and physiological body functions. Healthy eating habits, including the intake of fruits and vegetables, can modify the gut microbiota. This study aimed to demonstrate the effectiveness of a formulated fruits and vegetables supplement (FVS) in modulating the antioxidant capacity and the gut microbiota composition. We enrolled 30 healthy volunteer subjects, matched for age, gender, BMI, and smoking habits, and randomized into the FVS and the placebo (PLA) groups. Among the serum vitamins, the folic acid level resulted significantly higher (p=0.001) in FVS vs PLA, whereas the vitamin B2 level was significantly higher in the PLA vs FVS (p=0.028). The antioxidant capacity, measured by the ORAC method, resulted also slightly higher, but not reaching the statistical significance, in the FVS vs PLA. The dietary intake, assessed by 24hrs recalls, didn’t show any significant changes after the supplementation in both groups. The gut microbiome composition, measured by 16S rDNA sequencing, showed no difference in both alpha and beta diversity, whereas the LEfse analysis revealed a microbial shift after the treatment with a decreased abundance of the genus Ruminoccocus from the Lachnospiraceae family (p=0.009) and the unclassified genus from the family Erysipelotrichaceae (UC36, p=0.003) in the FVS vs PLA (confirmed by SIAMCAT analysis, AUC=74.1%). With a minor effect, also the genus Faecalibacterium and unclassified genus and family from the order Lactobacillales (UC31) were increased in the FVS vs PLA (p=0.0474, p=0.0352, respectively). SCFAs measurement by gas chromatography-mass spectrometry showed an increased level of 2-methylbutyrate in the FVS vs PLA (p=0.0385). Finally, the Spearman correlation analysis showed that, in the FVS group, the genus Faecalibacterium positively correlated with the 2-methyl butyrate (p=0.040). In the PLA group, none of the significant bacteria correlated with either SCFA or serum biomarkers. The network analysis confirmed the positive correlation between genus Faecalibacterium and the 2-methyl butyrate. We can conclude that FVS supplementation in healthy individuals modified the gut microbiota composition and metabolites, and it can potentially contribute to reduce the pro-inflammatory response along with the antioxidant capacity.